English-Speaking Skills Problems as Perceived by English Major Students: English - Virginia Gabrella Sengkey (Prodi Tadris Bahasa Inggris, 2024)
Understanding the challenges in English-speaking skills among English-major students is crucial for enhancing language learning. Hence, this research aimed to identify the English-speaking skills problems as perceived by the English-major students at a private university in North Sulawesi. This quantitative research used descriptive and comparative research designs. The study consisted of 95 English-major students taking Listening and Speaking classes. An instrument adapted from Irismet cited in Afshar and Asakereh (2016) was used to determine the English-speaking skills problems experienced by the students. The findings indicate the three main English-speaking skill problems of the students as perceived by them were that they lacked self-confidence in speaking in English in the class (M=3.49), had difficulty in finding an opportunity to practice speaking in English outside the class (M=3.32), and were highly anxious to speak English (M=3.25). Lastly, the findings showed no significant differences in the respondents’ perceptions of their English-speaking skills problems based on gender and class level.